FAKTOR YANG BERPENGARUH INDEKS HARGA SAHAM PADA BURSA EFEK INDONESIA TAHUN 2009 - 2012 - Supriyanto, Supriyanto; Mulyantini, Sri (Ekonomi dan Bisnis, 2016)
This study aimed to determine the effect of the exchange rate, inflation rate, and the SBI interest rate of commposite stock price index (CSPI) on the Stock Exchange by using the sample period from 2009 to 2012. Results Partially shows that exchange rate, have a significant effect on the index. SBI, have a significant and positive influence on the index. Inflation rate, has no sinifikan effect against JCI. While simultaneously showed that a difference significant between the Exchange Rate, Inflation and Interest Rates to JCI. The amount of Adjusted R Square of 0.714 or 71.4%. This figure gives the sense that the index change is influenced by the Exchange Rate, Inflation and Interest Rates 71.4%, for the remaining 28.6% nfluenced by other factors outside of this discussion.